Hypertonic Saline Infusion Acutely Degrades Mood in Healthy Volunteers (P23-014-19). (13th June 2019) - Suh, HyunGyu; Lieberman, Harris; Jansen, Lisa; Adams, J D; Seal, Adam; Butts, Cory; Colburn, Abigail; Kirkland, Tracie; Sprong, Cameron; Melander, Olle; Lemetais, Guillaume; Vanhaecke, Tiphaine; et al.
Abstract: Objectives: Mild and moderate dehydration adversely affect mood and cognitive function. During dehydration, hypertonic hypovolemia activates both osmo- and baro-receptors but it is not known which physiological pathway is associated with degraded mood state. This study examined the acute effect of osmoreceptor stimulation on mood. Methods: Sixty healthy adults (50% females, 30 ± 1 y; BMI: 26.9 ± 4.0 kg·m −2 ) were infused intravenously with 3.0% (HYPER) or 0.9% (ISO) NaCl for 2 h (0.1 ml·kg −1 ·min −1 ) using a counterbalanced, crossover design. Blood samples were collected every 30 minutes to measure plasma osmolality (POsm), copeptin (a surrogate marker of vasopressin), and renin-angiotensin-aldosterone system (RAAS) hormones. Mood was assessed with the short version of Profile of Mood State (POMS) questionnaire before and after the infusion. Results: POsm and copeptin increased from 286 ± 3 mmol·kg −1 to 305 ± 4 mmol·kg −1 and from 4.5 ± 3.7 pmol·L −1 to 20.4 ± 12.8 pmol·L −1, respectively in HYPER ( P < 0.05), and were unchanged in ISO ( P > 0.05). No hormonal differences were observed between trials for RAAS hormones ( P > 0.05). During HYPER copeptin, following the 2-h infusion, was greater in females than in males (female: 23.4 ± 13.9 pmol·L −1, male: 17.4 ± 10.9 pmol·L −1 ; P < 0.05). The POMS total mood disturbance (TMD) score increased from 10.5 ± 0.9 to 16.5 ± 1.6 in HYPER ( P < 0.05), but not in ISO ( P > 0.05). Among POMS subscales, depression-dejection and fatigue-inertia increased in HYPER compared to ISO ( P < 0.05). When TMD responses in the HYPER trial were analyzed with sex as a between-subjects factor, the increase was significant in females (pre: 10.2 ± 1.0, post: 18.6 ± 2.3; P < 0.001) but not in males (pre: 10.8 ± 1.4, post: 14.0 ± 2.0; P > 0.05). The confusion-bewilderment subscales and fatigue-inertia of the POMS were also elevated post HYPER in females ( P < 0.05), but not in ISO ( P > 0.05) in either sex. Conclusions: Hypertonic saline infusion acutely degrades mood state, and women appear to have a more pronounced response. The underlying mechanisms remain to be determined but may be related to higher copeptin levels in women. The study was registered at ClinicalTrials.gov as NCT02761434. Funding Sources: Danone Research. Supporting Tables, Images and/or Graphs: